Next generation of optodes coupling plastic antibody with optical fibers for selective quantification of Acid Green 16 - Mortari, Bianca [UNESP]; Khan, Sabir [UNESP]; Wong, Ademar [UNESP]; Fireman Dutra, Rosa Amalia; Taboada Sotomayor, Maria Del Pilar [UNESP] (Elsevier, 2020)
This work describes the development of a MIP-optode selective to Acid Green 16 (AG16) dye belong to the triphenylmethane family. The synthesis of the plastic antibody or MIP (molecularly imprinted polymers) was made by the bulk method directly onto the optical fiber surface which was used as a transducer in the optical sensor. The synthesized polymers were characterized by scanning electron microscopy, infrared with Fourier transform, attenuated total reflectance, and confocal optical microscopy. Experiments were performed to investigate the effects of pH, contact time, dye concentration, and temperature in the sensor response. Under optimized conditions were obtained a linear range from 100 μmol L−1 and 1.0 mmol L−1 with a limit of detection of 53 μmol L−1. The repeatability and reproducibility of MIP-optode were evaluated in terms of RSD, and the results obtained showed RSD values less 4%. Selectivity studies were carried out in presence of four other different dyes, and the signals obtained for these dyes confirmed the excellent selectivity of the developed sensor. The imprinting factor value founded for AG16 was 4.64 while for Direct yellow 50 was 1.4, for Direct Violet 51 was 0.7, for Acid Red 114 was 0.4 and for Acid Red 1 was 0.8. Finally, the proposed method was applied to measure acid green 16 in spiked real water samples. The recovery values founded were from 92% to 98% (experiments in triplicate), It was shown that the proposed optical sensor exhibited significant promise as a reliable technique for the selective detection of analyte acid green 16 in real water samples.
Keywords: Acid green 16; Biomimetic sensor; MIP; Optical fiber sensors; Optodes; Plastic antibodies; Selective adsorption